Origin and Transformation of Light Hydrocarbons Ascending at an Active Pockmark on Vestnesa Ridge, Arctic Ocean. Issue 1 (13th January 2020) - Pape, T.; Bünz, S.; Hong, W.‐L.; Torres, M. E.; Riedel, M.; Panieri, G.; Lepland, A.; Hsu, C.‐W.; Wintersteller, P.; Wallmann, K.; Schmidt, C.; Yao, H.; et al.
Abstract: We report on the geochemistry of hydrocarbons and pore waters down to 62.5 mbsf, collected by drilling with the MARUM‐MeBo70 and by gravity coring at the Lunde pockmark in the Vestnesa Ridge. Our data document the origin and transformations of volatiles feeding gas emissions previously documented in this region. Gas hydrates are present where a fracture network beneath the pockmark focusses migration of thermogenic hydrocarbons characterized by their C1 /C2+ and stable isotopic compositions (δ 2 H‐CH4, δ 13 C‐CH4 ). Measured geothermal gradients (~80 °C/km) and known formation temperatures (>70 °C) suggest that those hydrocarbons are formed at depths >800 mbsf. A combined analytical/modeling approach, including concentration and isotopic mass balances, reveals that pockmark sediments experience diffuse migration of thermogenic hydrocarbons. However, at sites without channeled flow this appears to be limited to depths >~50 mbsf. At all sites we document a contribution of microbial methanogenesis to the overall carbon cycle that includes a component of secondary carbonate reduction—that is, reduction of dissolved inorganic carbon generated by anaerobic oxidation of methane in the uppermost methanogenic zone. Anaerobic oxidation of methane and carbonate reduction rates are spatially variable within the pockmark and are highest at high‐flux sites. These reactions are revealed by 13 C depletions of dissolved inorganic carbon at the sulfate‐methane interface at all sites. However, 13 C depletions of CH4 are only observed at the low methane flux sites because changes in the isotopic composition of the overall methane pool are masked at high‐flux sites. 13 C depletions of total organic carbon suggest that at seeps sites, methane‐derived carbon is incorporated into de novo synthesized biomass. Key Points: Drilling with the seafloor drill rig MeBo70 revealed two major hydrocarbon sources beneath a pockmark at the crest of Vestnesa Ridge Thermogenic methane likely formed at depths >800 m below seafloor ascends through faults and leads to hydrate formation and seafloor emission Methane is transformed into dissolved inorganic carbon at all sites investigated with highest rates observed at active seafloor emission sites